Pendidikan Kesehatan Cuci Tangan Pakai Sabun dengan Video Terhadap Kemampuan Cuci Tangan pada Siswa SD - Ni Ketut Vera Parasyanti; Ni Luh Gede Puspita Yanti; I Gusti Agung Ayu Putri Mastini (Jurnal Akademika Baiturrahim Jambi, 2020)
Introduction : The problem that often happens to the school kids is related to hygiene and environment, one of them is washing off the hands with soap (CTPS). The prevalence of washing hands behavior is an increase from 47,0% to 49,8%. This research aims to analyze the impact of CTPS health education with video as the media toward the capability of washing the hands on the 3rd-grade students. Method : The pre-experimental design method with one group pretest design approach is used. The sample consists of 27 students who are chosen by the total sampling technique. Result : Before being given the CTPS health education, there are 24 children (88,9%) in the category of incapable to do the steps of CTPS, and there are 3 children (11,1%) in the category of capable to do it. After being given the CTPS health education, 25 children (92,6%) are in the capable category and 2 children (7,4%) are in the incapable category. Based on the result of Wilcoxon Sign Rank Test, it's known that p-value = 0,000 with (ɑ<0,05), it means that there is an impact from the health education of washing hands with soap by video as the media toward the capability of washing the hands on the 3rd student at Elementary School Number 1 Berangbang, Jembrana. Discussion : Based on that result, a CTPS health education by video as the media is recommended to increase the capability of washing the hands to the school kids.